PENGARUH SEMANGAT KERJA TERHADAP KOMITMEN KERJA DAN KINERJA PEGAWAI PADA PDAM KOTA TARAKAN - Hidayat, Muhammad Taufik; Grace Christien Sumakul (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to analyze the effect of work enthusiasm on work commitment and employee performance, as well as to examine the mediating role of work commitment at PDAM Kota Tarakan. This research falls under the category of explanatory research with a quantitative approach. The population, as well as the sample, consists of all employees of PDAM Kota Tarakan, totaling 103 individuals. Data analysis was conducted using path analysis techniques with the assistance of SmartPLS software. The results indicate that work enthusiasm has a positive and significant effect on employee performance (β = 0.344; p < 0.05) and work commitment (β = 0.778; p < 0.05). Additionally, work commitment also has a positive and significant effect on employee performance (β = 0.597; p < 0.05). An important finding of this study is that work commitment mediates the relationship between work enthusiasm and employee performance. Thus, increasing work enthusiasm not only directly impacts performance but also does so by strengthening employees' work commitment.